2020
DOI: 10.1037/gdn0000130
|View full text |Cite
|
Sign up to set email alerts
|

Individual perceptions of shared mental models of information and communication technology (ICT) and virtual team coordination and performance—The moderating role of flexibility in ICT use.

Abstract: Coordination and performance of virtual teams depend on the use of information and communication technology (ICT). Team members use many ICTs to collaborate with each other. Research has shown that shared mental models (SMM) improve team coordination and performance. Based on these results, we expect that for virtual teams, ICT SMM are positively related to team coordination and performance. Specifically, the relationship between ICT SMM and coordination is stronger if virtual team members have less flexibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 44 publications
5
32
0
Order By: Relevance
“…Globally H5 and 6 were confirmed: TOaCE and CWa predicted GHWB, showing how implicit coordination and adaptation to the team’s environment are group processes that determine not only the functioning of the team but also the socio-emotional climate that is created in it, including a climate of trust and greater satisfaction in its members. Likewise, as Müller and Antoni (2020) point out, this study also shows that the degree of knowledge and management of ICTs is important for establishing greater implicit coordination in the team, which in turn will allow to probably develop a favorable socio-emotional climate. The team’s ability to adapt to its environment and to the workload imposed by the task involves the division and distribution of tasks and support among team members.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Globally H5 and 6 were confirmed: TOaCE and CWa predicted GHWB, showing how implicit coordination and adaptation to the team’s environment are group processes that determine not only the functioning of the team but also the socio-emotional climate that is created in it, including a climate of trust and greater satisfaction in its members. Likewise, as Müller and Antoni (2020) point out, this study also shows that the degree of knowledge and management of ICTs is important for establishing greater implicit coordination in the team, which in turn will allow to probably develop a favorable socio-emotional climate. The team’s ability to adapt to its environment and to the workload imposed by the task involves the division and distribution of tasks and support among team members.…”
Section: Discussionsupporting
confidence: 57%
“…Work teams use them to share information quickly and effectively amongst members. To achieve high coordination for better performance and results, it is important that members have the same degree of knowledge and mastery over them ( Müller and Antoni, 2020 ). TOaCE refers to a climate of excellence, describing the shared concern for excellent quality in conducting tasks, associated with a shared vision or results.…”
Section: Introductionmentioning
confidence: 99%
“…Although these four individual ICT KSAs are important prerequisites for virtual team members, the challenges they address are the challenges at team level (i.e. team communication, information sharing and misunderstandings) rather than at an individual level (Müller and Antoni, 2019). In addition to individual ICT KSAs, team processes such as team cognition also influence the challenges of efficient team communication via ICTs.…”
Section: Media Theories and Information And Communication Technology Knowledge Skills And Abilitiesmentioning
confidence: 99%
“…Organizations can only benefit from virtual teams and ICT use, if their teams can apply ICTs without entailing additional workload for team members (Handke et al , 2018; Hantula et al , 2011). Empirical findings indicated that shared knowledge of ICTs leads to better ICT use (Thomas and Bostrom, 2007), knowledge transfer (Hasty et al , 2006) and team coordination and performance (Müller and Antoni, 2020). In contrast, unshared knowledge of ICT netiquette leads to misunderstandings and frustration among team members (Klitmøller and Lauring, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation